SNAP25-dependent membrane trafficking of the Kv1.5 channel regulates the onset of atrial fibrillation - Xuling Su; Beihua Shao; Zhiwen Chen; Hongcheng Gu; Ke Xiong; Guanghua Wang; Qicheng Zou; Yuting Cao; Caihong Zhang; Hongtao Xu; Yixin Yuan; Xuxia Zhao; et al. (Nature Communications)
Abstract Synaptosomal-associated protein 25 kDa (SNAP25) is essential for vesicular trafficking and protein docking at presynaptic membranes in the nervous system, yet its role in the heart remains poorly understood. Here, we show an unrecognized function of SNAP25, which is selectively expressed in the atria, in regulating atrial electrical remodeling and the onset of atrial fibrillation (AF). SNAP25 protein is downregulated in the atria of AF patients. Cardiomyocyte-specific knockout of SNAP25 in male mice significantly shortens the atrial effective refractory period and action potential duration (APD), increasing susceptibility to AF, which is attributed to elevated Kv1.5 current and membrane expression. Blocking Kv1.5 channels effectively restores atrial APD and reduces AF incidence. Mechanistically, SNAP25 deficiency reduces the internalization of Kv1.5 from the cell surface membrane to early endosomes. In human iPSC-derived atrial cardiomyocytes, SNAP25 deficiency similarly elevates arrhythmic activity and accelerates repolarization. In conclusion, this study reveals that SNAP25 regulates AF susceptibility by controlling the trafficking of the atrial-specific Kv1.5 channel, highlighting SNAP25 as a promising therapeutic target for atrial arrhythmias.